Pembelajaran Fisika Kuantum Menggunakan Model Blended Learning untuk Meningkatkan Kemampuan Berpikir Kritis - Aris Doyan; Susilawati Susilawati; Saprizal Hadi Saputra; Syamsul Hakim (Universitas Hamzanwadi, 2022)
This research was conducted in one class with a sample consisting of 42 students. This study aims to determine the improvement of students' critical thinking skills by implementing learning using the Blended Learning model. The results of this study are in the form of a description based on the value obtained from each critical thinking indicator and the average of the overall critical thinking indicators. Based on the results of the analysis, the average value of the critical thinking indicator score is 69.00, this shows that the Blended Learning learning model can help improve students' thinking skills in the critical category.